Life expectancy and survival analysis for companion dogs and cats in Seoul, South Korea - Yang, Isaac; Yoo, Dae-Sung; Min, Kyung-Duk (Frontiers in Veterinary Science, 2025)
BackgroundInvestigating life expectancy and mortality is crucial for the development of evidence-based health strategies for companion animals. However, relevant studies are lacking in South Korea, possibly because of challenges in collecting mortality data. In this regard, preliminary analyses were conducted to obtain life tables for companion animals in South Korea.MethodsThe electronic records of six veterinary hospitals in Seoul, South Korea were examined. The data collected included breed, sex, spay/neuter status, date of birth, and date of death for all dogs and cats with a verifiable date of death since November 1, 2004 until December 31, 2022. After data preprocessing, descriptive statistical analysis was performed to summarize the demographics, and life tables and survival curves were created for dogs and cats. Cox proportional hazards regression was used to analyze the effects of demographic factors on survival.ResultsThe mean age of dogs at death was 3427.49 days. Spayed or neutered dogs had a significantly higher life expectancy than intact dogs. Mixed-breed dogs had a higher life expectancy than purebred dogs. For cats, the mean age at death was 1965.49 days, with spayed or neutered cats living significantly longer than intact cats. Purebred cats had a higher median survival than Mixed-breed cats. Spaying or neutering and breed significantly affected survival probabilities in both species.ConclusionOur study provides insights into the longevity of companion animals in South Korea, and reveals that neutering and breed significantly influence life expectancy.